Opportunities and Challenges of Implementing the One Village One Product (OVOP) Model for Cooperative and Tourism Development in Southwest Sumba - Apriana H.J. Fanggidae; Efandri Agustian (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research examines the application of the One Village One Product (OVOP) model for cooperative and tourism development in Southwest Sumba, East Nusa Tenggara. Southwest Sumba has great potential in the co-operative and tourism sectors, but still faces major challenges in improving community welfare. OVOP, which began to be recognised in Japan in 1980, aims to empower communities by developing local superior products that can compete in the global market. This research uses a qualitative approach with interviews and documentation analysis to explore opportunities and challenges in implementing the OVOP model in Southwest Sumba. The results showed that although the OVOP programme can improve the competitiveness of local products and create business opportunities, the main challenges are limited infrastructure, weak management, and lack of human resource capacity. Therefore, stronger collaboration between the government, cooperatives, and tourism actors is needed to overcome these obstacles. In conclusion, the implementation of OVOP in Southwest Sumba can have a positive impact if supported by appropriate policies, increasing the capacity of business actors, and strengthening cooperatives as a forum for managing local superior products.